High school mathematics texts construction of statistics practices - Weiland, Travis (Frontiers in Education, 2023)
A robust understanding of statistics has become crucial in our data centric societies. In the school setting the teaching of statistics is situated within the mathematics curriculum in the U.S. However, many mathematics teachers often have little to no past experiences with statistics before teaching it. Given such circumstances, textbooks likely play a strong role influencing the statistics curriculum teachers enact for students. In this study, I investigate how the discourse of two common high school textbook series form what the actions are for doing statistics using a Foucauldian discourse analysis. I also contrast the findings of the analysis to the discourse of the field of statistics education, namely through the Guidelines for Assessment and Instruction in Statistics Education (GAISE II, Bargagliotti et al., 2020), highlighting some significant absences, and discussing implications for future research and curriculum development 1